Analisis Kualitas Buku Teks Matematika SMA Kelas X Kurikulum 2013 Edisi Revisi 2017 Berdasarkan Pendekatan Saintifik - Lisnasari Andi Mattoliang; Aufa Billah Arsyad; A. Sriyanti; Munirah (Alauddin Journal of Mathematics Education, 2022)
This study aims to determine the quality of the content of the mathematics textbook based on indicators in a scientific approach. This research is a descriptive study that describes or explains systematically the facts or characteristics of a particular population. The procedure in this study consisted of: (1) the preparation stage, by selecting the revised 2017 edition of the 2017 high school senior high school mathematics textbook, (2) conducting a literature study to find out how the quality of the mathematics textbook was based on a scientific approach, (3) drawing conclusions from the data obtained. has been obtained. Based on the results of the research that has been carried out, the quality of the mathematics textbooks is obtained in each chapter, namely in Chapter 1 as much as 60%, Chapter II as much as 70%, Chapter III as much as 50%, Chapter IV as much as 60%. As for the total number of chapters in textbooks based on a scientific approach as much as 60%. So it can be concluded that the quality of mathematics textbooks for class X 2013 curriculum based on the scientific approach is included in the sufficient category with the implementation of indicators in the scientific approach.